Axl activates autocrine transforming growth factor‐β signaling in hepatocellular carcinoma. Issue 3 (28th January 2015) - Reichl, Patrick; Dengler, Mirko; van Zijl, Franziska; Huber, Heidemarie; Führlinger, Gerhard; Reichel, Christian; Sieghart, Wolfgang; Peck‐Radosavljevic, Markus; Grubinger, Markus; Mikulits, Wolfgang
Abstract : In hepatocellular carcinoma (HCC), intrahepatic metastasis frequently correlates with epithelial to mesenchymal transition (EMT) of malignant hepatocytes. Several mechanisms have been identified to be essentially involved in hepatocellular EMT, among them transforming growth factor (TGF)‐β signaling. Here we show the up‐regulation and activation of the receptor tyrosine kinase Axl in EMT‐transformed hepatoma cells. Knockdown of Axl expression resulted in abrogation of invasive and transendothelial migratory abilities of mesenchymal HCC cells in vitro and Axl overexpression‐induced metastatic colonization of epithelial hepatoma cells in vivo . Importantly, Axl knockdown severely impaired resistance to TGF‐β‐mediated growth inhibition. Analysis of the Axl interactome revealed binding of Axl to 14‐3‐3ζ, which is essentially required for Axl‐mediated cell invasion, transendothelial migration, and resistance against TGF‐β. Axl/14‐3‐3ζ signaling caused phosphorylation of Smad3 linker region (Smad3L) at Ser213, resulting in the up‐regulation of tumor‐progressive TGF‐β target genes such as PAI1, MMP9, and Snail as well as augmented TGF‐β1 secretion in mesenchymal HCC cells. Accordingly, high Axl expression in HCC patient samples correlated with elevated vessel invasion of HCC cells, higher risk of tumor recurrence after liver transplantation, strong phosphorylation of Smad3L, and lower survival. In addition, elevated expression of both Axl and 14‐3‐3ζ showed strongly reduced survival of HCC patients. Conclusion : Our data suggest that Axl/14‐3‐3ζ signaling is central for TGF‐β‐mediated HCC progression and a promising target for HCC therapy. (Hepatology 2015;61:930–941)